Endophytic Bacteria Improve Plant Growth, Symbiotic Performance of Chickpea (Cicer arietinum L.) and Induce Suppression of Root Rot Caused by Fusarium solani under Salt Stress - Egamberdieva, Dilfuza; Wirth, Stephan J.; Shurigin, Vyacheslav V.; Hashem, Abeer; Abd_Allah, Elsayed F. (Frontiers in Microbiology, 2017)
Salinity causes disturbance in symbiotic performance of plants, and increases susceptibility of plants to soil-borne pathogens. Endophytic bacteria are an essential determinant of cross-tolerance to biotic and abiotic stresses in plants. The aim of this study was to isolate non–rhizobial endophytic bacteria from the root nodules of chickpea (Cicer arietinum L.), and to assess their ability to improve plant growth and symbiotic performance, and to control root rot in chickpea under saline soil conditions. A total of forty bacterial isolates from internal root tissues of chickpea grown in salinated soil were isolated. Four bacterial isolates, namely Bacillus cereus NUU1, Achromobacter xylosoxidans NUU2, Bacillus thuringiensis NUU3 and Bacillus subtilis NUU4 colonising root tissue demonstrated plant beneficial traits and/or antagonistic activity against F. solani and thus were characterized in more detail. The strain B. subtilis NUU4 proved significant plant growth promotion capabilities, improved symbiotic performance of host plant with rhizobia, and promoted yield under saline soil as compared to untreated control plants under field conditions. A combined inoculation of chickpea with M. ciceri IC53 and B. subtilis NUU4 decreased H2O2 concentrations and increased proline contents compared to the un-inoculated plants indicating an alleviation of adverse effects of salt stress. Furthermore, the bacterial isolate was capable to reduce the infection rate of root rot in chickpea caused by F. solani. This is the first report of F. solani causing root rot of chickpea in a salinated soil of Uzbekistan. Our findings demonstrated that the endophytic Bacillus subtilis strain NUU4 provides high potentials as a stimulator for plant growth and as biological control agent of chickpea root rot under saline soil conditions. These multiple relationships could provide promising practical approaches to increase the productivity of legumes under salt stress.